The Effects of Gender, Age, and Experience on Game Engagement. (September 2013) - Procci, Katelyn; James, Nicholas; Bowers, Clint
Entertainment gaming research typically focuses on the underlying motivations for play and on the subjective experience. A review of the literature has identified three factors that commonly affect patterns of play: gender, age, and gaming experience. This paper examines whether these individual differences affect the subjective experience of play, as measured by game engagement. Participants played a browserbased Flash game and responded to a number of surveys. The results suggested that low-levels of game engagement predict high-levels of game engagement, providing support for a proposed model of game engagement that exists on a gradient. The ability to experience low-levels of engagement while playing games is not affected by the individual differences of interest; however high-level engagement did decrease with age. Age may also weaken the relationship between low- and high-level game engagement.